Decentralization and local autonomy a framework for assessing progress - Ocampo, Romeo B. (Philippine Journal of Public Administration, 1991)
In light of the dangers posed by centralism, decentralization was initiated with the hope of furthering development especially in the local units. Decentralization aims to bring decisionmaking closer to the people and to deconcentrate benefits from the elite to the masses among others. Local autonomy has currently become the focal point in the decentralization process. However, there is still a need to further clarify the concept to reap more satisficing results. This article provides a framework to assess and evaluate the progress of and problems concomitant with decentralization and local autonomy.